2016
DOI: 10.1002/elan.201600459
|View full text |Cite
|
Sign up to set email alerts
|

Co2O3‐NH2‐MCM‐41 Decorated Graphite as an Effective Electrode: Synthesis, Characterization and its Application for Electro‐catalytic Oxidation of Acid Red 1

Abstract: 1IntroductionDyes have been extensively used for thousands of years in textile [1],p rinting [2],p igments [3] and other applications.N owadays,w ith the rapid development of industries,d yes play ac ritical role in many fields. These are however plentifully discharged, leadingt oe ffluents having strong acidity or alkalinity,l arge amounts of colored species, huge amount of surfactant and even various harmful heavy metals like Cu, Cr and Ni [4].T heir intense color could reduce the transmission of sunlight th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Ehrhardt et al indicated that Co 2 O 3 and Co 3 O 4 were likely to form simultaneously [ 43 ]. However, our sample was indexed to be mainly Co 3 O 4 (with 2θ = 19.0°, 36.9°, and 44.8° as described in PDF #42-1467) without the formation of Co 2 O 3 (whose XRD patterns are shown at 2θ = 51.2°, 56.3°, and 67.3° as described in PDF #02-0770 [ 44 ]). These results indicated that the hydrolysis reaction enabled the cobalt compound’s nucleation onto the GR sheets.…”
Section: Resultsmentioning
confidence: 99%
“…Ehrhardt et al indicated that Co 2 O 3 and Co 3 O 4 were likely to form simultaneously [ 43 ]. However, our sample was indexed to be mainly Co 3 O 4 (with 2θ = 19.0°, 36.9°, and 44.8° as described in PDF #42-1467) without the formation of Co 2 O 3 (whose XRD patterns are shown at 2θ = 51.2°, 56.3°, and 67.3° as described in PDF #02-0770 [ 44 ]). These results indicated that the hydrolysis reaction enabled the cobalt compound’s nucleation onto the GR sheets.…”
Section: Resultsmentioning
confidence: 99%